Unexpected synthesis, properties, and nonvolatile memory device application of imidazole-fused azaacenes - Zhao, Kexiang (2021)
The unexpected synthesis and characterization of imidazole-fused azaacenes are presented. Their optical and electrochemical properties have been investigated and compared with these of previously reported imidazole-fused azaacenes. Application of these two imidazole-fused azaacenes in memory devices showed distinctly different resistive behaviors.